Two‐Dimensional Haeckelite NbS2: A Diamagnetic High‐Mobility Semiconductor with Nb4+ Ions. Issue 34 (1st June 2017) - Ma, Yandong; Kuc, Agnieszka; Jing, Yu; Philipsen, Pier; Heine, Thomas
Abstract: In all known Group 5 transition‐metal dichalcogenide monolayers (MLs), the metal centers carry a spin, and their ground‐state phases are either metallic or semiconducting with indirect band gaps. Here, on grounds of first‐principles calculations, we report that the Haeckelite polytypes 1S ‐NbX2 (X=S, Se, Te) are diamagnetic direct‐band‐gap semiconductors even though the Nb atoms are in the 4+ oxidation state. In contrast, 1S ‐VX2 MLs are antiferromagnetically coupled indirect‐band‐gap semiconductors. The 1S phases are thermodynamically and dynamically stable but of slightly higher energy than their 1H and 1T ML counterparts. 1S ‐NbX2 MLs are excellent candidates for optoelectronic applications owing to their small band gaps (between 0.5 and 1 eV). Moreover, 1S ‐NbS2 shows a particularly high hole mobility of 2.68×10 3  cm 2  V −1  s −1, which is significantly higher than that of MoS2 and comparable to that of WSe2 . Abstract : Diamagnetic monolayers : Niobium in trigonal‐prismatic configuration is known to be in the 4+ oxidation state, for example, in NbX2 transition‐metal dichalcogenides. NbX2 in Haeckelite (square) configuration, however, is diamagnetic owing to the formation of an intermetallic bond across the square ring (see picture). These materials have small direct band gaps and high carrier mobilities, and are thus candidates for (opto)electronic applications.